Gastric Amyloidosis - Achmad Fauzi; Fajar Raditya; Ari Fahrial Syam; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Amyloidosis occurs as secondary to rheumatoid arthritis, inflammatory bowel disease and other diseases and also associated with familial Mediterranean fever. Outcomes are worse if there are cardiac or gastrointestinal manifestations. A 57 year-old female was admitted to our hospital with clinical manifestations of nausea, vomiting, epigastric pain, odynophagia, dysphagia and chronic diarrhea. She has also history of rheumatoid arthritis for 10 years. Upper gastrointestinal endoscopy revealed hyperemia in the whole region of gastric mucosa and lower gastrointestinal endoscopy showed hyperemia with erosion in colonic and ileal mucosa. Histopathologic examination of the gastric biopsy showed the deposition of amyloid materials in the mucosa. We report a case of gastric amyloidosis secondary to rheumatoid arthritis. Keywords: gastric amyloidosis, rheumatoid arthritis, dyspepsia